Remarkable solid-state fluorescence change from the visible to the near-infrared region based on the protonation/deprotonation of an AIEgen. (9th October 2020) - Li, Yangyang; Wang, Xian; Zhang, Lei; Liu, Luqi; Wang, Qiusheng; Lu, Hongguang; Zhao, Xiaowei
Abstract : An AIEgen exhibits a fluorescence switch between the visible and the NIR region upon acid/base stimuli, and accessible solid-state NIR emission. Abstract : The development of stimuli-responsive luminescent compounds featuring high solid-state emission and a long-wavelength fluorescence switch between the visible and the near-infrared (NIR) region is still a challenging task. Here we synthesize an aggregation-induced emission (AIE)-active luminogen DPP3A, which exhibits a fluorescence switch between the visible ( λ em, max = 652 nm) and the NIR region ( λ em, max = 800 nm) upon acid/base stimuli, and accessible solid-state NIR emission. NMR spectroscopy, theoretical calculations and powder X-ray diffraction are performed to acquire the mechanisms of acidochromism. The remarkable fluorescence changes on paper and banknotes of DPP3A present its potential as a security ink material with high contrast and easy accessibility that is free of background fluorescence.